2022
DOI: 10.1186/s43042-022-00331-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphism of human angiotensin-converting enzyme 2 gene locus and clinical severity of COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) is a devastating pandemic-causing disease with a variable severity among populations. Genetic studies have pinpointed angiotensin-converting enzyme 2 (ACE2), a key enzyme for viral entry, for its possible linkage to the disease progression. The present study aimed to investigate the potential association between single nucleotide polymorphisms (SNPs) of human ACE2 gene with the severity and outcomes of COVID-19 for better patient management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In addition, rs2048683 (T>G) was associated with T2D in East Asians [111] and blood pressure in European individuals (2020). Elbadri et al (2022) reported that the GG genotype (OR 5.852) is a potential marker for the risk of severe SARS-CoV-2 infection within Egyptian individuals [112]. Furthermore, this study reported a significant association between the TT and GT genotypes (p < 0.001) of rs2048683 with T2D [112].…”
Section: Inclusion and Exclusion Criteria For Selected Snpsmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, rs2048683 (T>G) was associated with T2D in East Asians [111] and blood pressure in European individuals (2020). Elbadri et al (2022) reported that the GG genotype (OR 5.852) is a potential marker for the risk of severe SARS-CoV-2 infection within Egyptian individuals [112]. Furthermore, this study reported a significant association between the TT and GT genotypes (p < 0.001) of rs2048683 with T2D [112].…”
Section: Inclusion and Exclusion Criteria For Selected Snpsmentioning
confidence: 56%
“…Elbadri et al (2022) reported that the GG genotype (OR 5.852) is a potential marker for the risk of severe SARS-CoV-2 infection within Egyptian individuals [112]. Furthermore, this study reported a significant association between the TT and GT genotypes (p < 0.001) of rs2048683 with T2D [112]. Together, these SNPs may be used as potential markers for T2D and risk of severe SARS-CoV-2.…”
Section: Inclusion and Exclusion Criteria For Selected Snpsmentioning
confidence: 60%